Community Councils: ¿Do they promote or discourage democracy in Venezuela? - Goldfrank, Benjamin (2011)
This article is an approach to the debate surrounding Venezuela´s community councils, a mechanism for citizen participation promoted, especially since 2005, by Hugo Chávez’s administration. After a brief description of the history and institutional characteristics of the community councils, the author describes academic production on the subject, identifying two opposing perspectives: one arguing in favor of their democratizing potential and the other arguing that the community councils are mechanisms at the service of the old logic of the political boss and are a threat to institutions of representative democracy. Based on a comparison between the community councils and other experiences of participatory democracy in Latin American, and taking into account a number of findings related to Venezuelan public opinion regarding the subject, the article analyzes both positions, identifying the limitations of each perspective.